Big Banks and Macroeconomic Outcomes: Theory and Cross-Country Evidence of Granularity - Franziska Bremus; Claudia M. Buch; Katheryn N. Russ; Monika Schnitzer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Does the mere presence of big banks affect macroeconomic outcomes? Gabaix (2011) shows that idosyncratic shocks can have aggregate effects if the distribution of firm sizes in manufacturing follows a power law distribution. Our contribution is two-fold. First, we expand the theory of granularity to encompass the Bertrand competition frequently used in models of banking. Using a model with banks of heterogenous size who charge endogenous markups, we show under which conditions granular effects emerge. Second, we empirically assess the relevance of granularity effects in banking using a linked micro-macro dataset of more than 80 countries for the years 1996-2009. We show that the banking sector is granular, i.e. the right tail of the bank size distribution follows a power law. Also, the presence of big banks as measured by high market concentration magnifies the effect of idiosyncratic shocks on loan growth. Through this channel, idiosyncratic shocks affecting large banks impact upon macroeconomic outcomes. This effect is particularly important for countries with less developed banking systems.
Keywords: E32; E44; G21; 330